2017
DOI: 10.1063/1.4986512
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for hard and soft substructures in thermoelectric SnSe

Abstract: SnSe is a topical thermoelectric material with a low thermal conductivity which is linked to its unique crystal structure. We use low-temperature heat capacity measurements to demonstrate the presence of two characteristic vibrational energy scales in SnSe with Debye temperatures thetaD1 = 345(9) K and thetaD2 = 154(2) K. These hard and soft substructures are quantitatively linked to the strong and weak Sn-Se bonds in the crystal structure. The heat capacity model predicts the temperature evolution of the unit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 43 publications
4
11
0
1
Order By: Relevance
“…Such a unique crystal structure may induce an ultralow κ l along the a-axis. Other studies showed that via heat capacity measurements, two characteristic vibrational energy scales in SnSe were revealed, which were corresponding to hard and soft substructures [111]. These distinct substructures derived from the strong bond divergence in SnSe, and the soft substructure was largely responsible for the thermal transport, which was consistent with the strong Umklapp scattering and low κ values observed in SnSe [111].…”
Section: Grüneisen Parametersupporting
confidence: 60%
“…Such a unique crystal structure may induce an ultralow κ l along the a-axis. Other studies showed that via heat capacity measurements, two characteristic vibrational energy scales in SnSe were revealed, which were corresponding to hard and soft substructures [111]. These distinct substructures derived from the strong bond divergence in SnSe, and the soft substructure was largely responsible for the thermal transport, which was consistent with the strong Umklapp scattering and low κ values observed in SnSe [111].…”
Section: Grüneisen Parametersupporting
confidence: 60%
“…Quantifying Anharmonicity through Raman Spectroscopy: We used the temperature-dependent polarized Raman spectroscopy data with z(xx)z and z(xy)z configurations from Ref [34] and modeled the temperature dependent shifts in the frequency of both E and A modes, [58][59][60][61][62][63] as described in the SI section.…”
Section: Characterization-electrical Resistivity and Seebeck Coefficimentioning
confidence: 99%
“…The discovery of high thermoelectric efficiency in a "simple" bulk material has added to the renewed interest in thermoelectric materials for energy harvesting applications, where waste heat is converted directly to electricity in reliable, low-maintenance semiconductor devices. The high performance in SnSe arises from the combination of an ultralow lattice thermal conductivity and a rapid increase in the thermoelectric power factor with temperature above 600 K. The low thermal conductivity has been attributed to highly anharmonic lattice dynamics [4][5][6][7][8], whereas the unusual, almost step-like changes of the electrical conductivity and Seebeck coefficient around 700 K have remained largely unexplained [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%